Efecto de abonos orgánicos en el cultivo del frejol arbustivo phaseolus vulgaris l - Tello Espinoza, Angel Polivio (2012)
On the Farm St. Agnes School of Agricultural Sciences, tested the effect of organic fertilizers in growing bush beans (Phaseolus vulgaris L.). The objectives were: 1.To determines the effect of organic fertilizers in the production of beans. 2. Select organic manure and dose 3.Conductbest behavior and economic analysis of the study treatments. Fertilizers were in vest gated bocashi, biol, humus, compost, absolute control and witness farmer. The six treatments were assigned to plots along the lines of random block design with four replications. The variables analyzed were: Days to germination, plant height at 15, 30, 45 and 60 days after sowing, days to flowering, days to harvest, number of pods per plant, weight of 100 grains, presence pest, yield per kg/ha and cost of production and profitability. The results showed significance in treatment compared to the control. Height grow thin the compost and biological excelled, beating all treatments, similar results were obtained in the number of pods per plant where the boil excelled, while the 100-grain weight and yield per hectare end the bocashi shoulder. The applications of organic fertilizers, in the volumes studied are economic, not generate a return above the one percent. The higher return bocashi treatment corresponded with a profit of $ 586,4 surpass all other treatments.